PROVISION OF SECONDARY MEDICAL CARE AND SANATORIUM-AND-SPA TREATMENT OF ATO PARTICIPANTS - Havlovskyi, O.D.; Holovanova, I.A. (World of Medicine and Biology, 2019)
Defenders of peaceful life, participants of the Anti-Terrorist Operation, have the right to benefits in various areas of social security, including health care. In accordance with the law, treatment of military personnel, prosthetics, medication and rehabilitation in specialized institutions are free of charge. The law stipulates that after the end of the basic course of treatment, veterans of the anti-terrorist operation can undergo a free health-improving and preventive course in the sanatorium, or receive compensation for it. According to experts, post-war symptoms tend to intensify over time, so all combatants need to restore the body’s psychological reserves. After all, the primary stress received during the combat actions is exacerbated by the secondary stress that occurs after returning home. The main institution in the general structure of medical institutions for the organization of medical assistance to veterans is a hospital in the village Tsybli, whose activity is under the patronage of the President of Ukraine. The list of sanatorium-and-spa institutions for ATO participants and persons with disabilities includes 85 institutions, among which 8 are located in the Poltava region.
Keywords: secondary medical care; combat veterans; sanatorium-and-spa treatment; participants of the anti-terrorist operation